Recreational anglers and fishing guides from an estuarine protected area in southeastern Brazil: Socioeconomic characteristics and views on fisheries management - Barcellini, Victor C. [UNESP]; Motta, Fabio S. [UNESP]; Martins, Alessandra M.; Moro, Pietro S. (Elsevier, 2013)
The Iguape and Cananéia Lagoon-Estuarine Complex is a biodiversity hotspot in southeastern Brazil. In recent decades, the region has become an important destination for recreational fishing. The objective of this study was to analyze the socioeconomic characteristics of visiting anglers and fishing guides working in the Cananéia-Iguape-Peruíbe Environmental Protected Area and their views on fisheries management. Data were collected through semi-structured interviews conducted between January 2009 and January 2010. We interviewed 278 anglers, who were predominantly male (93%) with a mean age of 47 years and from the state of São Paulo. The targeted species were snooks (Centropomus undecimales and Centropomus parallelus) and weakfishes (Cynoscion leiarchus and Cynoscion acoupa). Only half the anglers had the mandatory fishing license, and many of them lacked knowledge about catch quotas and minimum size requirements for specific species. The fishing guides (n = 80) were all male, with a mean age of 39 years and extensive experience. Most of the guides believe that the study area is somewhat degraded due to the removal of riparian vegetation, siltation, pollution, and especially the depletion of fish stocks. The opinions of the stakeholders (anglers and guides) converge on the high priority needs of the fishery and possible management actions regarding recreational fishing, such as improved fisheries enforcement (first in order of importance), proper training of fishing guides, zoning of fishing areas, and the definition of a maximum size limit. © 2013 Elsevier Ltd.
Keywords: Environmental Protected Area; Fisheries enforcement; Fisheries management; Recreational fishings; Riparian vegetation; Semi structured interviews; Socioeconomic characteristics; Southeastern Brazil; Biodiversity; Conservation; Economic and social effects; Environmental protection; Fisheries; biodegradation; biodiversity; estuarine environment; fish; fishery management; protected area; recreational activity; socioeconomic status; stakeholder; stock assessment; Brazil; Iguape; Sao Paulo [Brazil]